PENGARUH KOMPENSASI, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP RETENSI KARYAWAN PT. ENSEVAL PUTERA MEGATRADING BENGKULU - Irmansyah, Rudi; Ratnawili, Ratnawili (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
The study aims to analyze the influence of Compensation, job satisfaction, organizational commitment, and employee retention. The data collection technique uses a questionnaire and the data analysis technique uses multiple linear regression analysis. The results of this research prove that compensation, job satisfaction, organizational commitment, have an effect on employee retention. Keywords: Compensation, job satisfaction, organizational commitment, retention.